Roles of Alternative Sigma Factors in Invasion and Growth Characteristics of Listeria monocytogenes 10403S Into Human Epithelial Colorectal Adenocarcinoma Caco-2 Cell - Rukit, Junyaluck; Boonmee, Atsadang; Kijpornyongpan, Teeratas; Tulsook, Kan; Baranyi, József; Chaturongakul, Soraya (Frontiers in Microbiology, 2022)
Listeria monocytogenes is a Gram-positive facultative intracellular bacterium with a broad host range. With its housekeeping sigma factor and four alternative ones (namely SigB, SigC, SigH, and SigL), L. monocytogenes is able to express genes in response to changing environments. However, the roles of these sigma factors in intracellular survival are still unclear. The objectives of this study were to characterize the role of each alternative  factor on L. monocytogenes invasion and growth inside human epithelial colorectal adenocarcinoma Caco-2 cells. We used L. monocytogenes 10403S wild type and its 15 alternative sigma factor deletion mutants at multiplicity of infection of 100 and 1 in invasion and intracellular growth assays in the Caco-2 cells, respectively. At 1.5, 2, 4, 6, 8, 10, and 12 hours post-infection, Caco-2 cells were lysed and intracellular L. monocytogenes were enumerated on brain heart infusion agar. Colony forming units and growth rates were compared among strains. The results from phenotypic characterization confirmed that (i) SigB is the key factor for L. monocytogenes invasion and (ii) having only SigA (ΔsigBCHL strain) is sufficient to invade and multiply in the host cell at similar levels as the wild type. Our previous study suggested the negative role of SigL in bile stress response. In this study, we have shown that additional deletion of rpoN (or sigL) gene to ΔsigB, ΔsigC, or ΔsigH could restore the impaired invasion efficiencies of the single mutants suggesting absence if SigL could enhance host invasion. Therefore, we further investigated the role of SigL during extracellular and intracellular life cycles. Using RNA sequencing, we identified 118 and 16 SigL-dependent genes during extracellular and intracellular life cycle, respectively. The sigL gene itself was induced 5.0 folds prior to invasion and 5.3 folds during Caco-2 infection further suggesting the role of SigL in intracellular growth.